2000
DOI: 10.1021/ac001036c
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated 96-Well Liquid−Liquid Extraction for Analysis of Biological Samples by Liquid Chromatography with Tandem Mass Spectrometry

Abstract: A fully automated high-throughput liquid-liquid extraction (LLE) methodology has been developed for preparation of biological samples using a 96-well LLE plate and a 96-channel robotic liquid handling workstation. The 96-well LLE plate is made of a 96-well filter plate filled with inert diatomaceous earth particles, allowing continuous and efficient extraction of analytes between the aqueous biological sample and the organic extraction solvent. Two carboxylic acid-based protease inhibitor compounds with high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…Recently, electrospray ionization mass spectrometry (ESI/MS) and tandem mass spectrometry (MS/MS), coupled with high performance liquid chromatography, have been used increasingly in many areas of safety and clinical studies. 3,4 Since successful application of these techniques in the areas such as drug metabolism, pharmacokinetics, degradant identification and toxicology depends on a thorough understanding of the ESI/MS and MS/MS data of the compounds tested, the MS/MS data of protonated 1 are analyzed in detail in this report. As part of a continuous effort to analyze MS/MS data of novel drugs, 5 -7 this work reveals some unique features of the MS/MS spectra of this important class of farnesyl protein transferase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrospray ionization mass spectrometry (ESI/MS) and tandem mass spectrometry (MS/MS), coupled with high performance liquid chromatography, have been used increasingly in many areas of safety and clinical studies. 3,4 Since successful application of these techniques in the areas such as drug metabolism, pharmacokinetics, degradant identification and toxicology depends on a thorough understanding of the ESI/MS and MS/MS data of the compounds tested, the MS/MS data of protonated 1 are analyzed in detail in this report. As part of a continuous effort to analyze MS/MS data of novel drugs, 5 -7 this work reveals some unique features of the MS/MS spectra of this important class of farnesyl protein transferase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrospray ionization mass spectrometry (ESI/MS) and tandem mass spectrometry (MS n ) have been applied to many areas of drug discovery and development [2,3]. The successful application of these techniques requires a thorough understanding of the ESI/MS and MS n data of the drugs under investigation.…”
mentioning
confidence: 99%
“…Peng et al reported a fully automated high-throughput LLE method for the preparation of biological samples using a 96-well plate and 96-channel robotic liquid-handling workstation in order to completely automate the entire process. Extraction time was substantially shortened using this approach [130].…”
Section: Liquid-liquid Extraction (Lle)mentioning
confidence: 99%